I don't get how can we solve an equation by finding the inverse of that function. What has the inverse of that function got to do with solving the equation?
Function is:
f(x) = (x + 3) / (x -5)
Equation is:
(x+3) / (x-5) = 2
Please help ...
I don't get how can we solve an equation by finding the inverse of that function. What has the inverse of that function got to do with solving the equation?
Function is:
f(x) = (x + 3) / (x -5)
Equation is:
(x+3) / (x-5) = 2
Please help ...
So you want to solve f(x) = 2.
Apply the inverse function $\displaystyle f^{-1}$ to both sides:
$\displaystyle f^{-1}(f(x)) = f^{-1}(2)$.
But $\displaystyle f^{-1}(f(x)) = x$.
Therefore $\displaystyle x = f^{-1}(2)$.
So the solution to $\displaystyle \frac{x+3}{x-5} = 2$ is $\displaystyle x = f^{-1}(2)$.
You know how to find the inverse of $\displaystyle f(x) = \frac{x+3}{x-5}$ ? (No? This thread here might give you some clues ......)